Conjunctival Chemosis as a Specific Feature of Pseudomonas aeruginosa Corneal Ulcers. Issue 9 (September 2016) - Michael, Kaleena B.; Rotchford, Alan; Ramaesh, Kanna
Abstract : Purpose: Timely identification of a bacterial agent and its corresponding antibiotic sensitivity pattern is paramount in the management of infective corneal ulcers. Isolating the microbiological agents can take time; during this time, the initial therapy used is a chosen form of broad-spectrum antibiotics. There are no specific features of bacterial corneal ulcers that aid in identification of the involved pathogen with certainty. A clinical "marker" would undoubtedly be useful in the management of corneal ulcers. Methods: Early clinical photographs and clinical notes of 62 cases with confirmed infective corneal ulcers were examined by a masked reviewer. Results: Conjunctival chemosis was observed in 14 out of 16 cases of Pseudomonas aeruginosa –related corneal ulcers, as compared with 6 out of 46 cases caused by other organisms. The association between conjunctival chemosis and Pseudomonas aeruginosa is statistically significant, with P value <0.000001 and odds ratio 42.0 (7.2–470) using the Fisher exact test. Conclusions: Our findings suggest that conjunctival chemosis could be a useful marker to predict the presence of Pseudomonas aeruginosa in bacterial corneal ulcers.